Haitian migration and human rights: access to public health in a border region in Brazil (Research, Society and Development, 2019)
This work seeks to problematize social inequality expressed daily as an inequality in health. More precisely, it is inserted in a region of South America known as the triple Latin American border, a place of intense migratory flow. A privileged locus for discussing relations between migration and health. In this geographic context, the objective is to discuss migration - more specifically, Haitian migration in the context of border region in Brazil - and public health. To do so, we will conduct a discussion in the perspective of access to health as a human right for all people and the duty of the State. Discounts of quantitative and qualitative data. And through the dissemination of data, we will argue that the enjoyment of human rights is allowed in the entire border population, yet non-legalized foreigners residing or domiciled in Brazil (even legalized), does not enjoy rights in the same proportion as nationals.